Chemical composition of selected manganese nodules at various horizons inside core 710KH from campaign SO11 of R/V Sonne - Peter Stoffers; A Sioulas; Geoffrey P Glasby; Theo Thijssen (PANGAEA, 2023)
Surface as well as buried manganese nodules are found in core SO11_710KH. Buried manganese nodules are found at two horizons within the sediment column. These nodules show characteristic differences in their surface texture compared to surface nodules, but no marked difference in composition. The buried nodules are not associated with any well-defined feature such as a sedimentary hiatus. It is suggested that nodules are maintained at the sediment surface by bioturbation. Buried nodules are simply those nodules that have failed to be maintained at the sediment—water interface.